2015
DOI: 10.1016/j.ijrobp.2015.07.188
|View full text |Cite
|
Sign up to set email alerts
|

Use of Human Papillomavirus 16 (HPV16) Cell Free DNA for Assessment of Response to Chemoradiation in HPV-Associated Oropharyngeal Cancer

Abstract: much higher likelihood of cure. Several prognostic groupings have been proposed and we evaluate these in a large independent cohort. Materials/Methods: After institutional review board approval, an institutional database was queried for patients with HPV or p16 positive nonmetastatic oropharyngeal cancers treated with definitive radiation therapy (RT), and 247 cases were identified. Patient, tumor, and treatment factors were abstracted from the charts. Tested groupings included the American Joint Committee on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Similarly, plasma circulating tumor HPV16 DNA (ctHPV16DNA) is detectable in the majority of patients with HPV-associated OPSCC (12,(17)(18)(19)(20). Limited prior data have shown that ctHPV16DNA levels become largely undetectable after CRT in most patients, and that ctHPV16DNA levels may increase at the time of disease recurrence (12,(19)(20)(21). These prior studies retrospectively analyzed limited subsets of patients using real-time PCR.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, plasma circulating tumor HPV16 DNA (ctHPV16DNA) is detectable in the majority of patients with HPV-associated OPSCC (12,(17)(18)(19)(20). Limited prior data have shown that ctHPV16DNA levels become largely undetectable after CRT in most patients, and that ctHPV16DNA levels may increase at the time of disease recurrence (12,(19)(20)(21). These prior studies retrospectively analyzed limited subsets of patients using real-time PCR.…”
Section: Introductionmentioning
confidence: 99%
“…Blood-based biomarkers represent an ideal potential modality for the early detection or surveillance of HPV-associated cancers such as OPC and CEC. In the recent years ct-DNA has gained much attention as a method of investigating and monitoring tumor biology and clinical status [ 84 , 95 ]. Ongoing research is appraising the potential role of circulating HPV DNA in HPV-related cancers for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Serum HPV DNA can be also be used to monitor for any residual disease after CRT [ 83 ]. Limited prior data has shown that HPV16 ct-DNA levels become largely undetectable post-CRT in most patients, and that HPV16 ct-DNA levels may increase at the time of disease recurrence [ 83 , 84 ]. Dynamic variations of serum HPV ct-DNA levels are associated with response to treatment of localized or metastatic HPV-related OPC [ 80 , 83 , 85 ].…”
Section: Liquid Biopsy For Hpv Dna Detection In Cec and Opcmentioning
confidence: 99%
“…However, several practical issues, including harmonization of the assay to measure cf HPV DNA, still need to be addressed prior to its clinical implementation. Nonetheless, few groups have reported an association between such a biomarker and advanced nodal status and overall TNM stage, with potential utility in clinical prognostication and monitoring of treatment response 24 , 25 .…”
Section: Future Of Ebv Dna and Cf Tumor Dna Technologies In Head Andmentioning
confidence: 99%